BLENDED LEARNING – APPROACH, ADVANTAGES AND OPPORTUNITIES - BABAKHODJAEVA L.G. (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
The article looks at how blended learning approach has appeared after the introduction of distance learning. Blended learning is seen to be a compromise between traditional classroom learning environment and distance learning model. Models and components of blended learning are presented, as well as advantages and opportunities for students and academics in higher education.